Pendidikan Agama Kristen Bagi Remaja Di Era Globalisasi Berdasarkan Amsal 22:6 - Meilani Meilani; Martina Novalina (Sekolah Agama Kristen Terpadu Pesat Salatiga, 2022)
The era of globalization with rapid development and progress in various areas of life has had its own impact on human life, especially teenagers who always want to keep up with the times. The impact of the entry of the world in the life of teenagers not only brings good influences but also bad influences. This paper aims to examine the impact and influence of the process of globalization on adolescents in Indonesia as well as the role of Christian Religious Education (PAK) in educating adolescents based on the verse contained in Proverbs 22:6. The research method used is a descriptive qualitative method by conducting literature research through the excavation of various sources of literature both from the Bible, books, various journals related to PAK for adolescents, the era of globalization, and the exegesis of Proverbs 22:6. The result of this article's research is that teenagers are unstable but already have their own perceptions or thoughts. According to Proverbs 22:6 adolescents are educated according to the path they understand or according to the perception of the teenager himself. PAK is here to educate, direct and build the right habituation so that the thoughts of teenagers who have been illuminated by the truth are the way that is appropriate of him.AbstrakEra globalisasi dengan perkembangan dan kemajuan pesat dalam berbagai bidang kehidupan telah memberi dampak tersendiri bagi kehidupan manusia, terutama remaja yang selalu ingin mengikuti perkembangan zaman. Dampak dari masuknya dunia dalam kehidupan remaja tidak hanya membawa pengaruh baik tetapi juga pengaruh buruk. Tulisan ini bertujuan untuk meneliti dampak dan pengaruh proses globalisasi terhadap anak remaja di Indonesia serta peran Pendidikan Agama Kristen (PAK) dalam mendidik remaja berlandaskan ayat yang terdapat dalam Amsal 22:6. Metode penelitian yang dipakai adalah metode kualitatif deskriptif dengan melakukan penelitian pustaka melalui penggalian berbagai sumber literatur baik dari Alkitab, buku, berbagai jurnal yang berkaitan dengan PAK bagi remaja, era globalisasi, dan eksegesis Amsal 22:6. Hasil dari penelitian artikel ini adalah remaja merupakan pribadi yang labil tetapi sudah memiliki persepsi atau pemikirannya sendiri. Berdasarkan Amsal 22:6 remaja dididik sesuai dengan jalan yang dipahaminya atau menurut persepsi remaja itu sendiri. PAK hadir untuk mendidik, mengarahkan dan membangun pembiasaan yang benar agar pemikiran remaja yang sudah diterangi oleh kebenaran itulah yang menjadi jalan yang patut baginya.